Analisis Pendapatan dan Margin Pemasaran Usaha Ekspor Karang Hias di PT. Agung Aquatic Marine Denpasar Bali - Andi Arwandi; Andi Rusdi Walinono; Ilyas Ilyas (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Indonesia's 2.5 million hectares of coral reefs include 569 species, or about 67% of the world's 845 coral species. One of the companies engaged in the export business of ornamental corals is PT Agung Aquatic Marine located in Bali province. This study aims to determine the costs, revenues and marketing margins of ornamental coral export business at PT Agung Aquatic Marine, Denpasar Bali. This research uses descriptive quantitative. Data analysis used is income analysis, marketing margin and marketing efficiency. The results showed that the costs incurred amounted to Rp2,472,069,157 so that the revenue earned was Rp822,355,543, There are two types of marketing margins used in the sale of ornamental coral euphyllia type, the first from fishermen to exporters and then to consumers which totaled Rp2,078,202, while the second from suppliers and then to exporters after that to consumers amounting to Rp2,017,637. The efficiency level of Marketing channel I is 13.1% and marketing channel II is 5.7%. So it can be seen that obtaining high margins and profits is Marketing channel I. While the one with the most efficient marketing is Marketing channel I. While the one with the most efficient marketing is Marketing Channel II.